El análisis de la pobreza y la campaña contra la mendicidad en la Ciudad de México, 1929-1931 - Lorenzo Río, María Dolores (El Colegio de México, A.C., 2018)
This article explores the classifications, stigmas, values and norms that defined the typology of urban poverty and formed the basis of policies towards the beggars of Mexico City between 1929 and 1931. The history of social policy has focused its attention above all on the beneficiaries of social security (workers, single mothers, orphans) and there are few references to the dispossessed poor, who were beneficiaries of the social policies of the post-revolutionary period. Based on the documents and publications on the study of begging that were prepared by Eyler Simpson and Ramon Beteta for public welfare agencies, the author shows how benefits for those considered dispossessed were differentiated from social security, which was considered a right of workers.